2022
DOI: 10.36253/phyto-13454
|View full text |Cite
|
Sign up to set email alerts
|

Fusarium annulatum causes Fusarium rot of cantaloupe melons in Spain

Abstract: During the summer of 2018, there was high incidence of fruit rots of cantaloupe melons (Cucumis melo var. cantalupensis) in Murcia province, south-eastern Spain. The fruits showed development of whitish mycelium and pulp softening. Morphological and molecular analysis of the internal transcribed spacer (ITS), translation elongation factor 1-α (TEF1-α) and the second largest subunit of RNA polymerase (RPB2) genes confirmed Fusarium annulatum as the causal agent of the disease. A phylogenetic study indicated tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 23 publications
0
8
0
Order By: Relevance
“…It is primarily reported as the causal agent of ear rot in maize; however, studies also reported the pathogen as responsible for symptoms of seedling decay and stalk, crown and root rot in maize [19,26,27]. F. annulatum, first described by Bugnicourt et al [28], is a species associated with symptoms of rot in different crops, such as cantaloupe melons in Spain and saffron in China [29,30]. The name F. annulatum is often confused with F. proliferatum, a well-known maize pathogen associated with crown and root rot [15,31].…”
Section: Discussionmentioning
confidence: 99%
“…It is primarily reported as the causal agent of ear rot in maize; however, studies also reported the pathogen as responsible for symptoms of seedling decay and stalk, crown and root rot in maize [19,26,27]. F. annulatum, first described by Bugnicourt et al [28], is a species associated with symptoms of rot in different crops, such as cantaloupe melons in Spain and saffron in China [29,30]. The name F. annulatum is often confused with F. proliferatum, a well-known maize pathogen associated with crown and root rot [15,31].…”
Section: Discussionmentioning
confidence: 99%
“…Regarding the pathogenicity of other Fusarium species, F. annulatum has also been reported to cause fruit-corm and root rot in crop plants such as melon and onion, as well as medicinal-aromatic plants such as Blettila striata L. and saffron, in addition to grapevine. [31][32][33][34]. These studies indicate that F. annulatum is pathogenic in many hosts.…”
Section: Dry Root Weigth 2022 2023mentioning
confidence: 74%
“…Interestingly, keanumycin A is extremely effective in inhibiting Botrytis cinerea (MIC = 69 nM / 80 μg L –1 ), which is a devastating phytopathogen that causes Botrytis blight, also known as gray mold, in over 1000 plant species and was ranked as the second most important plant-pathogenic fungus . To a lesser extent, it also inhibited the growth of Alternaria solani, the causative agent of early blight in tomatoes and potatoes, but not of Fusarium annulatum, which can infest different fruits , and is additionally an opportunistic human pathogen.…”
Section: Resultsmentioning
confidence: 99%